Selling a natural community: Exploring the role of representations in promoting a new urban development. (August 2014) - Opit, Simon; Kearns, Robin
Abstract We explore the rhetoric and symbolism deployed in the course of selling residential properties at Hobsonville Point, a new development in Auckland. Specifically, we ask what understanding of community is promoted in this development, and how this understanding is represented in promotional material. Our study is informed by analysis of newspaper articles, promotional material and planning/legal documents as well as field observation (2011–2012). We conclude that appealing to a contemporary yearning for nature and social cohesion at an urban coastal location has generated a situation in which community is being 'sold' at Hobsonville Point, yet paradoxically is yet to be found.